2019
DOI: 10.1161/circulationaha.118.036065
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional and Proinflammatory Regulatory T-Lymphocytes Are Essential for Adverse Cardiac Remodeling in Ischemic Cardiomyopathy

Abstract: Background. Heart failure (HF) is a state of inappropriately sustained inflammation, suggesting the loss of normal immunosuppressive mechanisms. Regulatory T-lymphocytes (Tregs) are considered key suppressors of immune responses; however, their role in HF is unknown. We hypothesized that Tregs are dysfunctional in ischemic cardiomyopathy and HF, and promote immune activation and left ventricular (LV) remodeling. Methods. Adult male wild-type (WT) C57BL/6 mice, Foxp3-diptheria toxin receptor(DTR) transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
195
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(220 citation statements)
references
References 49 publications
4
195
1
6
Order By: Relevance
“…More recent studies have demonstrated that Th1 cells are not significantly enhanced in the heart in chronic ischemic HF, in contrast to Th17 cells, Th2 cells, and dysfunctional Tregs, which dominate chronic ischemic cardiomyopathy; this supports that the CXCR3-Th1 recruitment axis does not play a role in chronic ischemic HF. (22,38). In contrast, we and others have demonstrated that T cells are pathogenic and induce adverse cardiac remodeling in response to cardiac pressure overload (4, 5, 21).…”
Section: Discussionmentioning
confidence: 92%
“…More recent studies have demonstrated that Th1 cells are not significantly enhanced in the heart in chronic ischemic HF, in contrast to Th17 cells, Th2 cells, and dysfunctional Tregs, which dominate chronic ischemic cardiomyopathy; this supports that the CXCR3-Th1 recruitment axis does not play a role in chronic ischemic HF. (22,38). In contrast, we and others have demonstrated that T cells are pathogenic and induce adverse cardiac remodeling in response to cardiac pressure overload (4, 5, 21).…”
Section: Discussionmentioning
confidence: 92%
“…A persistent inflammatory response to injury (ischaemic, infectious, pressure, or volume overload), or a failure to resolve inflammation following acute injury, can lead to chronic expression of pro‐inflammatory cytokines that have been suggested to contribute to HF progression . Moreover, the failing heart exhibits expanded populations and activation of both innate and adaptive immune cells that are essential contributors to progressive LV remodelling . Pro‐inflammatory cytokines such as TNF‐α, IL‐1β, and IL‐6 are associated with increasing severity of HF and contribute to progressive LV remodelling and systolic dysfunction …”
Section: Discussionmentioning
confidence: 99%
“…Heart failure (HF) is a pro‐inflammatory state . Several pathways including pro‐inflammatory cytokines and innate and adaptive immune cellular responses have been implicated in HF . It is also evident that dysregulated inflammation and immune activation contribute importantly to progressive left ventricular (LV) remodelling and dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Водночас гени сімейства NFATC беруть участь у регуляції IL-2 залежної імунної відповіді [9]. Останніми дослідженнями також встановлено, що певні субпопуляції Т-клітин мають захисну функцію щодо розвитку фібротичних процесів у міокарді, а в експериментальних моделях доведена відновлювальна роль цих клітин при експериментальному міокардіальному фіброзі [10]. Експресія імунокомпетентних клітин встановлена також при патоморофологічних перетвореннях, пов'язаних із розвитком неопластичних процесів ендометрія [11].…”
unclassified
“…При цьому фіброз стулок у дітей з ДАК, на відміну від групи порівняння, з перебігом цієї вади без фібротичних змін на клапані, супроводжувався зменшенням залежності діаметра кореня аорти від величини експресії NFATC1 та появою більш потужних його зв'язків з МШП та ЗСЛШ, появою позитивних взаємозв'язків між експресією NFATC1 та рівнем сироваткового кальцію, а також між CD25 + та CD95 + субпопуляціями лімфоцитів. Встановлені факти щодо змін субпопуляційного складу лімфоцитів, кальцієвого обміну та високої експресії NFATC1 у дітей з ДАК при розвитку клапанного фіброзу, з одного боку, підтверджують описану в літературі протективну роль клітин імунної відповіді при патологічних змінах міокарда [10], а з іншого, свідчать про особливу роль цього гену у процесах транскрипційної регуляції морфогенетичної перебудови, що відбувається при розвитку фіброзу стулок. У зв'язку з цим, підвищена активність NFATC1 може бути розцінена як компенсаторна у відповідь на збільшення діаметра аорти, що супроводжує клапанний фіброз при ДАК з розвитком подальших ефектів гіперрегуляції у вигляді підвищення ітерлейкін-2-залежної фракції лімфоцитів та зниження активності апоптозу за рахунок відносного зменшення вмісту CD95 + їх субпопуляції.…”
unclassified